2011 IEEE 11th International Conference on Data Mining Workshops 2011
DOI: 10.1109/icdmw.2011.144
|View full text |Cite
|
Sign up to set email alerts
|

Rating: Privacy Preservation for Multiple Attributes with Different Sensitivity Requirements

Abstract: Motivated by the insufficiency of the existing framework that could not process multiple attributes with different sensitivity requirements on modeling real world privacy requirements for data publishing, we present a novel method, rating, for publishing sensitive data. Rating releases AT (Attribute Table) and IDT (ID Table) based on different sensitivity coefficients for different attributes. This approach not only protects privacy for multiple sensitive attributes, but also keeps a large amount of correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 15 publications
0
46
0
Order By: Relevance
“…Aiming to protect privacy information with multiple sensitive attributes, Yang Xiaochun [9] proposed a multiple sensitive attributes technology based on multi-dimensions buckets and described 3 corresponding algorithms according to greed method. Document [10] proposes an algorithm to classify multiple sensitive attributes which is to satisfy privacy protection by assign different sensitivity coefficients to different sensitive attributes. Document [11] proposes (k, l) module which assigns every degree of anonymity and the diversity of privacy attribute values of data items and achieves degree of anonymity and diversity with personalization.…”
Section: Introductionmentioning
confidence: 99%
“…Aiming to protect privacy information with multiple sensitive attributes, Yang Xiaochun [9] proposed a multiple sensitive attributes technology based on multi-dimensions buckets and described 3 corresponding algorithms according to greed method. Document [10] proposes an algorithm to classify multiple sensitive attributes which is to satisfy privacy protection by assign different sensitivity coefficients to different sensitive attributes. Document [11] proposes (k, l) module which assigns every degree of anonymity and the diversity of privacy attribute values of data items and achieves degree of anonymity and diversity with personalization.…”
Section: Introductionmentioning
confidence: 99%
“…As a part of this study various techniques have been identified and studied that could be used to preserve the user"s data sensitivity. The techniques namely Anonymization [6,7,8], Perturbation [9], Blocking based approach [10], Cryptographic techniques [11], Condensation approach [12,13] have been studied. Each of these techniques had come up with their own advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…Perturbation of data is a very easy and effective method for protecting sensitive information of the data from unauthorized users. This approach of perturbation is discussed in [3].there are two types of data perturbation for protecting data namely [4]: 1. Probability distribution approach (or) Data Swapping: This approach takes the data and replaces it from the same distribution sample or from the distribution itself.…”
Section: A Data Perturbationmentioning
confidence: 99%